PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF GENDER RELATIONS IN THE UPBRINGING OF A HARMONIOUSLY DEVELOPED GENERATION - Dadaboyeva Dildora Ablakulovna (Journals Park Publishing, 2025)
This article presents a theoretical analysis of the pedagogical and psychological aspects of gender relations in the upbringing of a well-rounded generation. The study examines the manifestation of gender equality principles at all levels of education—school, college, and university—and explores the role of gender sensitivity in the personal development of young individuals. Gender equality is interpreted not only as a legal or political concept but also as a cultural, moral, and spiritual value within educational processes. By comparing Western and national-religious approaches, the article substantiates the need for a culturally adaptive national gender education model tailored to the Uzbek context. The article is based on a theoretical-methodological approach and provides a scholarly foundation for future applied research.
Keywords: Gender equality, pedagogy, psychological approach, youth development, education system, cultural values, stereotypes, gender sensitivity.